Therapeutic Potential of Bioactive Flavonoids from Citrus Fruit Peels toward Obesity and Diabetes Mellitus - Kaihui Lu; Yew Mun Yip (MDPI AG, 2023)
Obesity is associated with a significantly increased risk of cardiovascular and metabolic diseases such as diabetes mellitus. Recently, a growing body of evidence shows that phytochemicals, especially many flavonoids, place an inhibitory regulatory effect on adipogenesis, obesity and diabetes. With computer-aided drug discovery, the action modes of more and more bioactive flavonoids are being identified and confirmed at the molecular level. Citrus fruit peels are particularly rich in bioactive flavonoids which have demonstrated strong therapeutic potentials in regulating lipid metabolisms. However, they are usually thrown away after consuming the flesh, sometimes even causing environmental problems. Thus, extraction of useful flavonoids from citrus fruit waste for pharmaceutical industry could be a profitable and environmentally friendly solution in the future, advocating the concepts of circular economy and sustainable society. The aim of this review is to summarize current evidence on the antiobesity and antidiabetic potentials of identified bioactive flavonoids extracted from the peels of citrus fruits. Our results suggest that various citrus fruit peels could be potential sources for novel drugs and nutraceuticals. Combining experimental data and artificial intelligence methods to study citrus flavonoids would facilitate the discovery of novel drugs against obesity and obesity-related metabolic diseases.